1996
DOI: 10.1002/j.1460-2075.1996.tb00510.x
|View full text |Cite
|
Sign up to set email alerts
|

White collar-1, a central regulator of blue light responses in Neurospora, is a zinc finger protein.

Abstract: The Neurospora crassa blind mutant white collar‐1 (wc‐1) is pleiotropically defective in all blue light‐induced phenomena, establishing a role for the wc‐1 gene product in the signal transduction pathway. We report the cloning of the wc‐1 gene isolated by chromosome walking and mutant complementation. The elucidation of the wc‐1 gene product provides a key piece of the blue light signal transduction puzzle. The wc‐1 gene encodes a 125 kDa protein whose encoded motifs include a single class four, zinc finger DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
419
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 436 publications
(428 citation statements)
references
References 52 publications
6
419
0
3
Order By: Relevance
“…WC proteins have been well characterized in the filamentous ascomycete Neurospora crassa (Ballario et al, 1996;Linden and Macino, 1997;Froehlich et al, 2002;He et al, 2002), and homologues have been identified in ascomycetes, basidiomycetes, and zygomycetes (for review, see Corrochano, 2007 (Idnurm and Heitman, 2005;Lu et al, 2005). WHITE COLLAR orthologues are also encoded in the genome of A. nidulans (Greene et al, 2003), and the corresponding gene products have recently been shown to influence light sensing, sexual development, and mycotoxin production (Purschwitz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…WC proteins have been well characterized in the filamentous ascomycete Neurospora crassa (Ballario et al, 1996;Linden and Macino, 1997;Froehlich et al, 2002;He et al, 2002), and homologues have been identified in ascomycetes, basidiomycetes, and zygomycetes (for review, see Corrochano, 2007 (Idnurm and Heitman, 2005;Lu et al, 2005). WHITE COLLAR orthologues are also encoded in the genome of A. nidulans (Greene et al, 2003), and the corresponding gene products have recently been shown to influence light sensing, sexual development, and mycotoxin production (Purschwitz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…WC proteins have been well characterized in the filamentous ascomycete Neurospora crassa (Ballario et al, 1996;Linden and Macino, 1997;Froehlich et al, 2002;He et al, 2002), and homologues have been identified in ascomycetes, basidiomycetes, and zygomycetes (for review, see Corrochano, 2007). For example, Phycomyces blakesleeanus mutants defective in blue-light-dependent phototrophism may contain mutations in the madA gene, which encodes a protein similar to WC-1 of N. crassa (Idnurm et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In Neurospora, all known light responses are mediated by blue light, and almost all responses require the protein products of two genes, white collar-1 (wc-1) and wc-2 (Degli Innocenti and Russo 1984;Lakin-Thomas et al 1990;Collett et al 2002;He et al 2002;Lee et al 2003). The cloning of the two wc genes by Macino and coworkers (Ballario et al 1996; revealed that they are both PER-ARNT-SIM (PAS) domaincontaining transcription factors with GATA type Zn-finger DNA-binding domains. WC-1 contains three PAS domains, while WC-2 has only one PAS domain.…”
mentioning
confidence: 99%
“…WCs autoregulate their own transcription and their post-translational modifications (Ballario et al 1996;Talora et al 1999;Schwerdtfeger and Linden 2000). wc-1 is an immediate early light-inducible gene.…”
mentioning
confidence: 99%
“…In N. crassa, blue light regulates induction of carotenoid pigment production [2,3], protoperithecia (sexual fruiting body) formation [4], phototropism of perithecial beaks [5] and circadian rhythm. All of above mentioned phenomenon are abolished by mutations in wc-1 or wc-2 [6,7,8]. Trichoderma atroviride, a fungus used in biological control, sporulates in a synchronized manner following a brief pulse of blue light.…”
Section: Introductionmentioning
confidence: 99%